2016
DOI: 10.1177/2473011416s00112
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Intense Therapeutic Ultrasound for the Treatment of Chronic Plantar Fasciitis

Abstract: Initial treatment of plantar fasciitis (PF), consisting of anti-inflammatories, stretching and in-shoe orthosis (heel pad, heel wedge, or arch support), leads to symptomatic resolution in over 90% of patients but takes 3-6 months. This study was conducted to test the effectiveness of a minimally invasive modality, intense therapeutic ultrasound (ITU), in accelerating the healing of chronic plantar fasciitis (PF). ITU uses high-frequency high-intensity focused ultrasound to create small thermal injury zones ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Ninety-four randomized controlled trials (5397 participants) assessed pain in the short term as an outcome. Of these, 51 randomized controlled trials (2937 participants) compared 14 different therapeutic interventions to the control group in the short term: acupuncture ( n = 69 19,20,23 ); botulinum toxin ( n = 161 27,31,33,34 ); corticosteroid injection ( n = 244 107,108,168,186 ) ; dry needling ( n = 215 39,41,42 ); extracorporeal shock wave therapy ( n = 863 54,55,65,71,72,75,78,81,84,166 ); low-dye taping ( n = 213 106,115,119,231 ); low-level laser therapy ( n = 231 122,125,133,129,132 ); micronized dehydrated human amnion/chorion membrane injection ( n = 175 92,93 ), myofascial releases ( n = 101 212,214,215,222 ); orthosis ( n = 259 141,148,160,162 ); platelet-rich plasma ( n = 110 181,186 ); radiofrequency ( n = 87 236,237 ); stretching ( n = 112 230,231 ); and therapeutic ultrasound ( n = 97 250,251 ). A summary of the meta-analysis performed to compare interventions versus controls is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Ninety-four randomized controlled trials (5397 participants) assessed pain in the short term as an outcome. Of these, 51 randomized controlled trials (2937 participants) compared 14 different therapeutic interventions to the control group in the short term: acupuncture ( n = 69 19,20,23 ); botulinum toxin ( n = 161 27,31,33,34 ); corticosteroid injection ( n = 244 107,108,168,186 ) ; dry needling ( n = 215 39,41,42 ); extracorporeal shock wave therapy ( n = 863 54,55,65,71,72,75,78,81,84,166 ); low-dye taping ( n = 213 106,115,119,231 ); low-level laser therapy ( n = 231 122,125,133,129,132 ); micronized dehydrated human amnion/chorion membrane injection ( n = 175 92,93 ), myofascial releases ( n = 101 212,214,215,222 ); orthosis ( n = 259 141,148,160,162 ); platelet-rich plasma ( n = 110 181,186 ); radiofrequency ( n = 87 236,237 ); stretching ( n = 112 230,231 ); and therapeutic ultrasound ( n = 97 250,251 ). A summary of the meta-analysis performed to compare interventions versus controls is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is assumed that calf stretches are a profitable treatment at the initial stage of rehabilitation program [6]. A study [7] stated that noninvasive therapy showed more reduction of heel pain in chronic plantar fasciitis. A newly emerging technology has gained momentum over the past three decades in treating injuries of soft tissue, even though its acceptance rate and scientific evidence remains diverse.Low-power lasers are effectively utilized to enhance healing of wounds, reduction of pain and inflammation for all musculoskeletal injuries.…”
Section: Introductionmentioning
confidence: 99%